Pengaruh Analisis Fundamental Sentimen Pasar Dan Inflasi Terhadap Tingkat Pengembalian Saham Pada Bank BNI dan BRI - Rachmad Ibrahim; Nabil Sada Amerie; Wahyu Adi Nugroho; Maria Yovita R.Pandin (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the influence of fundamental analysis, market sentiment, and inflation on stock returns at Bank BNI and BRI for the 2022–2024 period. The method used is a quantitative approach with multiple linear regression using secondary data including financial ratios (ROA, ROE, DER, EPS, and PER) as proxies for fundamental analysis, changes in the Jakarta Composite Index (JCI) as a proxy for market sentiment, and inflation proxies taken from data from the Central Statistics Agency (BPS). The results show that these three variables have a positive but insignificant effect on stock returns. The R² value of 0.593 indicates that fundamental analysis, market sentiment, and inflation explain 59.3% of the variation in stock returns, while the remainder is influenced by other factors outside the model. The direction of this positive relationship is in line with Signaling Theory, which emphasizes that fundamental information and macroeconomic conditions are important signals for investors.